Importance of Soft Skills in Project Management - Swasti Suvasweta Satpathy, Dr. Anupama Jena , (International Journal of Scientific Research and Management (IJSRM), 2017)
Project management is one of the areas of business management, where a project manager has the sole responsibility to manage the project effectively. So, project manager needs a number of skills to handle the project. Though before becoming a project manager he acquires all the formal educations and gathers experiences, he needs managerial skills which can be otherwise said as soft skills. It refers to some non-technical skills such as leadership, communication, coordination, decision making, negotiation, etc. Although these are not directly related to the outcome of the project, they have a lot of importance in all the phases of a project. Hard skills or technical skills like creating work break down structure, preparing schedule plan, preparing budget plan, etc. are very important but the output of such plans cannot be incorporated without the above mentioned soft skills.